Sealing Efficiency of MTA, Accelerated MTA, Biodentine and RMGIC as Retrograde Filling Materials - Mutluay Merve; Mutluay Abidin Talha (Balkan Stomatological Society, 2021)
Background/Aim: This in-vitro study evaluated the apical-sealing ability of MTA, MTA+10% CaCl2, Biodentine™ and RMGIC when used as retrograde material.